Demotivating factors in teaching mathematics: A study of Albanian teachers - Pepkolaj, Lekë; Arnal-Palacián, Mónica; Begué, Nuria; Prahmana, Rully Charitas Indra (IKIP Siliwangi and I-MES, 2024)
Several studies have highlighted the existence of demotivated teachers in schools. There are several demotivating factors that influence the decisions and commitment that a teacher can acquire. The literature review allows us to characterize the factors that different authors identify to explain teacher demotivation. This article aims to analyze some of the factors that influence mathematics teachers' demotivation and the evaluation of the degree of demotivation in relation to work environment, teaching autonomy, extrinsic values, and students. The information was collected from a questionnaire consisting of 24 items, which was given to 121 active Albanian teachers teaching at different levels of education. These data were analyzed using a quantitative methodology. The independent variables gender, teacher's age, qualification, pupils' age, and type of school are also considered to perform a multivariate analysis. From the results obtained, we can state that the factors that generate the greatest demotivation are textbooks, political conversion and corruption, aspects related to the curriculum, and the costs they must bear. In addition, school status, curriculum changes, meritocracy, material costs, autonomy, and research significantly explain the demotivation of public sector teachers. It highlights the need to seek structured responses aimed at regulating teaching careers.